2001
DOI: 10.1159/000050579
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Improvement and Remission Rates after Thymectomy for Myasthenia gravis

Abstract: Background: Thymectomy has become an accepted option in the treatment of myasthenia gravis (MG). However, the optimal selection of patients for surgery remains controversial. Objective: The objective of the study is to define factors influencing improvement and remission rates after thymectomy for MG. Methods: We retrospectively reviewed our experience in the surgical management of patients with MG over the last 20 years, and analyzed if patient’s age, sex, preoperative Osserman Stage, thymic histology, durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This was also elucidated in a previous local study consisting of 10 myasthenia gravis patients who had clinical improvement after thymectomy ( 29 ). Also, it was found that myasthenia gravis with mild severity, including those with pure ocular involvement, seems to have better outcome and higher remission rate, which is consistent with previous studies ( 24 , 30 32 ). Poor outcome after thymectomy was seen more frequently in patients whose myasthenia gravis symptoms occurred before the age of 50 years.…”
Section: Discussionsupporting
confidence: 90%
“…This was also elucidated in a previous local study consisting of 10 myasthenia gravis patients who had clinical improvement after thymectomy ( 29 ). Also, it was found that myasthenia gravis with mild severity, including those with pure ocular involvement, seems to have better outcome and higher remission rate, which is consistent with previous studies ( 24 , 30 32 ). Poor outcome after thymectomy was seen more frequently in patients whose myasthenia gravis symptoms occurred before the age of 50 years.…”
Section: Discussionsupporting
confidence: 90%
“…De Perrot et al [8] found that 81% of their patients improved after thymectomy. Postoperative improvement was greater in patients with advance MG and thymic hyperplasia (P = 0.04).…”
Section: Continuedmentioning
confidence: 97%
“…When compared to thymoma, the presence of thymic hyperplasia has been associated with either more improvement or CSR rates. [ 12 13 16 17 ] However, some other reports have found no significant difference concerning the prognosis of MG between patients with and without thymoma. [ 18 19 ] In our cohort, the frequencies of CSR, PR, and MM were comparable between patients with thymic hyperplasia and thymoma.…”
Section: Discussionmentioning
confidence: 99%